The Marcus Garvey and Universal Negro Improvement Association Papers. - Hill, Robert A., 1943-; Garvey, Marcus, 1887-1940; Forczek, Deborah; Tolbert, Emory J. (University of California Press, 1984)
This is the third volume of Robert A. Hill's massive ten-volume survey of Marcus Mosiah Garvey and the extraordinary mass movement of black social protest he inspired. Hill brings together a wealth of original documents-speeches, letters, newspaper articles, intelligence reports, pamphlets, and diplomatic dispatches--to provide a record of the period between the first and second international conventions of the Universal Negro Improvement Association. The succ.